Poláčkův Hostinec U kamenného stolu - Všetička, František (Stylistyka, 2021)
Karel Polacek, a Czech prose writer of Jewish origin, is famous for his humorous novel Hostinec u kamenneho stolu [The Stone Table Tavern}, which was published in 1941 during German occupation. In that time his authorship was shielded by an artist Vlastimil Rada. It is really surprising that Polacek (writing when expecting his physical extermination) could write such a cheerful, humorous and highly artistic work. Special attention has been paid to three couples of people, not identical twins, but individuals very much alike. Specifically two sisters, two brothers and two suitors dominate there. Into the bargain there is a reappearing anticipatory figure and deus ex machina. The novel creates a compositional “dyad”, the story is divided into two unmarked parts. This piece of prose is built up on a color principle - the combination of blue and yellow. The individual chapters have synoptic titles, which is very common in humorous and satirical literature. The final part has the character of quantitative effect - the wedding ceremony gathers many different people; quantity intensifies the quality of the end. Karel Polacek died at the end of the Second World War in a concentration camp.